PERAN GURU SEBAGAI MOTIVATOR DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA SISWA KELAS III PADA PELAJARAN BAHASA INDONESIA DI SD MUHAMMADIYAH 1 LIMBOTO - Rahmi Intan Usman; Lamsike Pateda; Wiwik Pratiwi (Al-mujahidah, 2026)
This study aims to determine the role of teachers as motivators in developing the reading skills of third-grade students and to determine the supporting and inhibiting factors in improving students' reading skills in Indonesian language lessons at Muhammadiyah 1 Limboto Elementary School. The type of research used is descriptive qualitative research with a field research approach. Data were obtained through observation, interviews, and documentation. Data analysis techniques were carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have a very important role as motivators in improving students' reading skills. Forms of motivation provided include giving praise, awards, and the application of interesting and enjoyable learning methods. Supporting factors for the success of teacher motivation include support from the school through morning literacy activities, the availability of reading corner facilities, and active student participation in reading activities. Inhibiting factors include low interest in reading at home, the influence of gadgets on learning habits, and limited learning time at school. Efforts made by teachers to overcome these obstacles are by increasing reading activities in class, building communication with parents, and providing ongoing motivation to students.